GROWTH RATE AND NUTRIENT APPARENT DIGESTIBILITY IN MEXICAN CUINO PIGS - C. Lemus; J. Bonilla; F. Grageola; M. G. Orozco; R. Almaguer; J. Ly (Journal of Animal and Plant Sciences, 2012)
Performance traits and nutrient apparent digestibility were evaluated in fourteen males (castrated) and females (1:1) Mexican Cuino pigs with a mean initial weight 20 kg. Pigs were fed a 14% crude proteincommercial diet ad libitum for12 weeks and nutrient digestibility was determined at the end of growth trial. There was no difference (P>0.05) in feed intake between females and castrated males Cuino pigs, no sex effect was observed on feed conversion. Overall, Cuino pigs showed a slow growth rate. Total apparent digestibility of dry and organic matter was similar in both sexes, but N digestibility was significantly higher in females than in castrated males. Organic matter digestibility was significantly (P<0.05) correlated with dry matter (r, 0.454) and N (r, 0.802) digestibility. There were no significant (P>0.05) interdependence among performance traits and nutrient digestibility. It is considered that is necessary to obtain more information related to performance traits and nutrient digestibility of Mexican Cuino pigs, as affected by different factors which could influence these indices. On the other hand, this study shows that there are signs that females shows better performance and digestibility of nutrients than castrate males.
Keywords: Cuino pigs; performance traits; digestibility